The relative contribution of the most important signs of motor and functional performance of some of the offensive skills of football players ages ( 20-30 ) years - A. D. Wissam Hameed A. D. Ali Asfour (physical education and sport sciences college for women/ Baghdad University, 2019)
A search on the four-door, as it contained the first door on the front and the importance of research, and touched a researcher of the importance of testing and measurement in the field of sports, especially football game as well as the focus was on the most important motor and functional capacity and some offensive skills, came the importance of research to identify the percentage contribution of the motor and functional capacity the performance of the offensive skills of footballers applicants, either the research problem lies on the need to know the coaches percentage contribution of the motor and functional capacity to perform some offensive skills in football, either the areas of research included the human domain that represents my players advanced in Maysan province for the sports season (2016 -2017) , temporal area and determine the duration of the (06/25/2017) to very (07/30/2017), while the domain spatial golf clubs Maysan province. The researcher used the descriptive survey manner , the sample consisted search (80) Player of the players applicants , and the researcher applying kinetic and functional tests of offensive skills and a game of football ( agility , flexibility , compatibility, efficiency of the circulatory system and the heart, anaerobic capacity short , handling, Ro-Ro , scoring ) , as was the use of the system ( SPSS ) to get the search results, The researcher concluded that the mobility and functional capacity contributed well proportioned in the performance of some offensive skills in football as well as devise a final predictive equation by which to predict offensive skills in terms of the most important motor and functional abilities of football players to the category of applicants , So the researcher recommends the need to the attention of the trainers side motor and functional as one of the basic requirements that affect athletic performance